Evaluation of organic solvents efficiency for ink samples extraction / Nur Atiqah Zaharulli - Zaharulli, Nur Atiqah (Universiti Teknologi MARA Cawangan Pulau Pinang, 2020)
Questioned document examination becomes a great interest and one of the broad fields in forensic science. It involves the analysis of ink, handwriting and signature examination, paper's physical structure analysis and the ageing of a document. Ink analysis in forensic document examination is a challenging process. Questioned documents examiners are dealing with unknown source of ink and minute sample size. Ink extraction needs to be done before the ink analysis. 17 gel pen ink samples were chosen in this study. Solubility test has been done to determine the degree of solubility of ink in a variety of organic solvents. Extraction solvent optimization is a process to evaluate the efficiency of organic solvents to extract ink samples. Ethanoic acid showed the ability to dissolve most of the ink samples and displayed maximum absorbance of UV-Vis spectra.